Functional Outcome of Distal Third Tibia Fractures Treated with Minimally Invasive Plate Osteosynthesis - Muhammad Nadeem Kashmiri, Raja Adnan Ashraf, Muhammad Shehryar Zia, Asif Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: As the highest number of complications are associated with the distal tibia fracture it is one of the most challenging condition to treat. Minimally invasive plate osteosynthesis techniques are more feasible. As the disappointing results were obtained from the traditional techniques therefore this method was gradually evolved. Study design: It is a prospective study conducted in Pakistan Railway General Hospital, Rawalpindi for the duration of one year from January 2022 to December 2022. Material and Methods: The study comprised of 49 patients who fulfilled the inclusion criteria. Among 49 patients there were 23 males and 26 female patients. The patients that were not fulfilling the inclusion criteria were excluded from the study. Results: 40% of the patients had problem in the right leg and 60% had it in their left side. There were 24 patients that reported about fibula plating the remaining 52% had no fibula plating experienced. The mean time of surgery was 7 days ranging from 3 to 8 days. Based on the classification of fracture, 72% patients were included in the 43A category and 43B included 28% patients. Conclusion: For distal tibia fractures, minimally invasive plate osteosynthesis has better radiological and functional outcomes and is quite better than other treatment methods. The invasive method can cure these fractures with fewer complications and in a short union time. Keywords: distal tibia fractures and soft tissue.